Among the gentiles: Greco-Roman religion and Christianity - Johnson, Luke Timothy (The Anchor Yale Bible reference library, 2009)
Presenting a fresh inquiry into early Christianity and Greco-Roman paganism, Luke Timothy Johnson begins with a broad definition of religion as a way of life organized around convictions and experiences concerning ultimate power